Psychometric Properties of the Contour Drawing Rating Scale (Testing on a Russian Sample) - A.A. Zolotareva (Экспериментальная психология, 2023)
Body image disorders are closely associated with eating disorders, suicidal thoughts and intentions. In foreign science and practice, the Contour Drawing Rating Scale (CDRS) by M. Thompson and J. Gray is widely used for diagnosing body image disorders. The purpose of the present study was to adapt the CDRS on a population sample of Russian-speaking respondents. Five hundred and sixty respondents completed the Russian-language versions of the CDRS, Eating Disorder Inventory (EDI), and the Depression, Anxiety, and Stress Scale-21 (DASS-21). To assess the convergent and concurrent validity of the Russian CDRS, the r-Pearson correlation coefficient was used. Sex and age differences in body image were examined using the Student's t-test and one-way analysis of variance (ANOVA). Results showed that real and ideal body images according to the CDRS correlated statistically significantly with the EDI and DASS-21 scores, as well as reported weight and BMI. These findings proved the convergent and concurrent validity of the adapted instrument. Females and older respondents reported a greater discrepancy between real and ideal body images than did males and younger respondents. In conclusion, the Russian CDRS showed convergent and concurrent validity.